Bioprospecção do fungo Lasiodiplodia theobromae MMPI para produção integrada de biomassa micelial e β-glucana - Marchioro, Marcelo Luis Kuhn (2022)
The production of mycelial biomass and exocellular βDglucan (lasiodiplon) by the fungus Lasiodiplodia theobromae MMPI was studied as an integrated biotechnological platform. Sucrosebased culture media and soybean molasses were evaluated for the fungus cultivation. Experimental design and response surface methodology were employed to define conditions that maximize mycelial production and to analyze the coproduction of lasiodiplodan, a (1→6) Dglucan with biological properties of biomedical relevance. Central composite rotational design 23 (DCCR 23) was used to evaluate the influence of substrate concentration (total sugars), rice bran extract concentration (nitrogen source) and agitation speed on mycelial growth and lasiodiplodan production. The biomasses produced were characterized in terms of proximal composition, amino acid and lipid profile, antioxidant potential, content of total phenolics and bioactive compounds, thermogravimetric profile and morphological characteristics. The composition of the culture medium was decisive in defining the quantities of mycelial biomass and lasiodiplodan produced, as well as the quality and nutritional composition of the biomasses. The conditions that promoted the greatest mycelial growth were 64.43 gL1 of total sugars, 8.81 of rice bran extract and 152.8 rpm of agitation in a medium based on soybean molasses. Such culture condition promotes a production of 12.44 gL1 of lasiodiplodan. Sucrosebased medium contributed to higher production of lasiodiplodan. The biomasses produced in both media showed appreciable protein content (16.27 g100g1 and 19.88 g100g1). The biomass from the medium formulated with soy molasses presented all essential amino acids and in concentrations higher than the biomass produced in medium with sucrose. Soybean molasses also promoted the production of lipidrich biomass (43.76 g 100 g1), especially unsaturated fatty acids (32.67 g 100 g1), with emphasis on the polyunsaturated content (27, 42 g 100g1) such as gammalinoleic acid (24.38 g 100g1) and alphalinolenic acid (2.99 g 100g1). The extracts obtained from both biomasses, although containing low contents of total phenolics, present considerable antioxidant potential against ABTS, DPPH, hydroxyl radicals and reducing power of ferric and molybdenum VI ions. Gallic acid and catechin were the major compounds among the biocompounds identified in the biomass extracts. Cinnamic acid was identified in both extracts and pcoumaric acid in the molasses biomass extract. Thermogravimetric analyzes showed that both biomasses present thermal stability considering industrial conditions commonly used in the food and feed industries. The results obtained indicate the technical potential of an integrated production of mycelial biomass and lasiodiplodan from both culture media, which are low cost. The mycelial biomasses produced in sucrose and soy molasses medium have potential as an ingredient especially for animal feed due to their composition in proteins, lipids, dietary fiber and mineral content. Another important aspect to be highlighted is that the high lipid content found in the biomass produced in soybean molasses indicates for the first time the fungus L. theobromae MMPI as an oleaginous microorganism, with prospects for exploration of biofuels and fatty acids.